2020
DOI: 10.3390/molecules25194434
|View full text |Cite
|
Sign up to set email alerts
|

3,7-Dihydroxytropolones Inhibit Initiation of Hepatitis B Virus Minus-Strand DNA Synthesis

Abstract: Initiation of protein-primed (-) strand DNA synthesis in hepatitis B virus (HBV) requires interaction of the viral reverse transcriptase with epsilon (ε), a cis-acting regulatory signal located at the 5’ terminus of pre-genomic RNA (pgRNA), and several host-encoded chaperone proteins. Binding of the viral polymerase (P protein) to ε is necessary for pgRNA encapsidation and synthesis of a short primer covalently attached to its terminal domain. Although we identified small molecules that recognize HBV ε RNA, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Bulky substitution in positions R 1 , R 2 and R 3 leads to a decreased inhibitory activity, indicating that sulfonyl- or lactone substituents can increase the efficacy [ 190 , 191 , 193 ]. These findings have been validated by recent studies, which also highlighted the increased efficacy of amide-substituted α-HTs [ 194 , 195 , 196 ].…”
Section: Novel Therapeutic Strategiessupporting
confidence: 64%
“…Bulky substitution in positions R 1 , R 2 and R 3 leads to a decreased inhibitory activity, indicating that sulfonyl- or lactone substituents can increase the efficacy [ 190 , 191 , 193 ]. These findings have been validated by recent studies, which also highlighted the increased efficacy of amide-substituted α-HTs [ 194 , 195 , 196 ].…”
Section: Novel Therapeutic Strategiessupporting
confidence: 64%
“…In collaboration with Le Grice and co-workers, it was recently found that 3,7-dihydroxytropolones are capable of inhibiting initiation of HBV minus strand DNA synthesis. [23] Unfortunately, cytotoxicity of the compounds precluded observing any antiviral activity of the 3,7-dihydroxytropolones previously tested (e. g., 4 a). Consistent with these prior results, none of the 3,7-dihydroxtropolones tested had selective anti-HBV activity (4 b-g and 15).…”
Section: Hepatitis B Virus Antiviral Activitymentioning
confidence: 99%
“…[14][15][16] Typically, (di) hydroxylated tropolones have strong cytotoxic, antimicrobial and antiviral activities when three adjacent oxygens are present, which allows chelation of up to two metal ions (e.g., Fe 2+ , Zn 2+ , Cu 2+ , Mg 2+ ) and thus enables the (un)competitive inhibition of (bi) metallic enzymes such as the medically relevant inositol monophosphatase, matrix metalloproteases and virulence factors (e.g., anthrax lethal factor or HIV reverse transcriptase). 9 Compound 5, e.g., was shown to inhibit the initiation of DNA synthesis of the hepatitis B virus 17 and is furthermore highly cytotoxic against cultured B16 melanoma cells, thereby substantially extending the life span of mice with B16 melanoma. 15 Recent studies suggest that the cytotoxic effects of tropolones (in multiple myeloma cells) may be due to the alteration of cellular iron availability.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Compound 5, e.g. , was shown to inhibit the initiation of DNA synthesis of the hepatitis B virus 17 and is furthermore highly cytotoxic against cultured B16 melanoma cells, thereby substantially extending the life span of mice with B16 melanoma. 15 Recent studies suggest that the cytotoxic effects of tropolones (in multiple myeloma cells) may be due to the alteration of cellular iron availability.…”
Section: Introductionmentioning
confidence: 99%